Microvascular coupler device versus hand‐sewn venous anastomosis: A systematic review of the literature and data meta‐analysis. Issue 5 (4th April 2020) - Maruccia, Michele; Fatigato, Giusy; Elia, Rossella; Ragusa, Luigi Amerigo; Vestita, Michelangelo G.; Nacchiero, Eleonora; Robusto, Fabio; Nicoli, Fabio; Pedro Ciudad,; Giudice, Giuseppe
Abstract: Background: Successful vascular anastomosis is essential for the survival of free tissue transfer. The aim of the study is to review the current literature and perform a meta‐analysis to assess the potential advantages of a mechanical anastomosis coupler device (MACD) over the hand‐sewn (HS) technique for venous anastomoses. Methods: A systematic Medline search was performed to gather all reports of articles related to MACD from 1984 until now. The following data were extracted: first author and publication date, study design, number of patients and anastomosis, coupler size, site and type of reconstruction, venous anastomotic time, flap failure. A meta‐analysis was performed on articles that met the following inclusion criteria: studies comparing MACD and HS technique in venous anastomosis, reporting anastomotic time, and postoperative complications. Results: Thirty‐three studies were included for the analysis. Twenty‐four were retrospective case series and nine were retrospective comparative studies. A total of 12, 304 patients were enrolled with a mean age of 49.23 years (range 31–72). A total of 13, 669 flaps were accomplished. The thrombosis rate recorded with MACD was 1.47%. The meta‐analysis revealed that MACD significantly decreased anastomotic time (standard difference in means = −0.395 ± 0.105; Z = −3.776; p  < .001) and postoperative flap failure risk (odds ratio [OR] = 0.362, 95% confidence interval [CI] = 0.218–0.603, Z = −3.908, p  < .001), but it did not decrease postoperative venous thrombosis risk (OR = 0.504, 95% CI = 0.255–1.129, Z = −1.666, p = .096). Conclusions: MACDs are a safe and effective alternative to traditional anastomosis. The anastomotic coupler is easier, much faster, and requires less technical skills than a HS microvascular anastomosis.